The Development of Value-Added Potential in Products of Community Enterprises Entrepreneurs in Nonthaburi Province of Thailand - Phromphithakkul, Wasin (Journal of Public Administration Chiang Rai Rajabhat University, 2023)
The objectives of this article are: To study the potential development of creating added value in products of community enterprises entrepreneurs in Nonthaburi province of Thailand. The potential development in this time is divided into 4 steps: 1) the importance of measuring the potential development of adding value in the product 2) measuring the development of the potential to create added value in the product 3) the component of the potential development creation of added value in products and 4) indicators that measure the components of the development of potential to create added value in products of community enterprises entrepreneurs, namely (1) product factors (2) process factors (3) ) staff performance factors, (4) personal learning factors, (5) factors for compensation of community enterprise members, (6) factors for information technology acceptance, and (7) strategic placement factors.